Identification and mechanism prediction of mulberroside A metabolites in vivo and in vitro of rats using an integrated strategy of UHPLC-Q-Exactive Plus Orbitrap MS and network pharmacology - Zhang, Xiao; Dong, Pingping; Song, Jian; Zhang, Huimin; Wang, Feiran; Liu, Yuecheng; Yan, Yingying; Li, Linlin (Frontiers in Chemistry, 2022)
Mulberroside A is a polyhydroxylated stilbene active component of Morus alba L. Studies have shown that it has antitussive, antiasthmatic, tyrosinase and antioxidation activities. However, little is known about the metabolism of it in vitro and in vivo. In our study, an integrated strategy on the basis of UHPLC-Q-Exactive Plus Orbitrap MS and network pharmacology was established to comprehensively research the metabolic characteristic of mulberroside A for the first time. Plasma, urine, feces and liver tissues of rats in the blank group and drug group were collected after intragastric administration of mulberroside A at a dose of 150 mg/kg, and rat liver microsomes were cultured for in vitro metabolism experiment. The biological samples were processed by different methods and analyzed in positive and negative ion modes using UHPLC-Q-Exactive Plus Orbitrap MS. A total of 72 metabolites were finally identified based on the accurate molecular mass, relative retention time, MS/MS spectra and related literatures combined with the Compound Discoverer 3.1. The metabolic pathways were mainly hydrolysis, glucuronidation, hydrogenation, sulfation, hydroxylation, methylation and their composite reactions. In addition, a network pharmacology method was used to predict the mechanism of action of mulberroside A and its metabolites. In the end, 7 metabolites with high gastrointestinal absorption and drug-likeness and 167 targets were screened by Swiss ADME and Swiss Target Prediction. 1702 items of GO analysis and 158 related signaling pathways of KEGG were enriched using Metascape. This study established a novel integrated strategy based on UHPLC-Q-Exactive Plus Orbitrap MS and network pharmacology, which could systematically analyze the metabolism behavior of mulberroside A in vivo and in vitro of rats and provide basis for the further research of mulberroside A.